A precursor of Aflatoxin B1, Versicolorin A, impairs the mitochondrial function of human intestinal Caco-2 cells - Thierry Gauthier; Sylvie Puel; Ophelie Rocher; Isabelle P. Oswald; Olivier Puel (Environment International)
Versicolorin A (VERA) is a mycotoxin produced by Aspergillus section Flavi species that is frequently detected in foodstuffs, particularly in corn. VERA is a precursor of aflatoxin B1 (AFB1), which is currently considered to be the most hazardous mycotoxin. While AFB1 has been shown to impair oxidative phosphorylation (OXPHOS), the impact of VERA on mitochondrial function has not been extensively documented until now. The aim of the present study was to investigate the effect of VERA on mitochondrial function in intestinal Caco-2 cells. To this end, OXPHOS was assessed by measuring the oxygen consumption rate using the Seahorse™ real-time analyzer. In contrast to AFB1, a low concentration of VERA (5 µM) was a strong uncoupler of OXPHOS and inhibited respiratory complexes I and III within a few minutes of exposure. After 24 h of exposure, VERA reduced the transcription of all mitochondrial genes encoding proteins involved in the electron transfer chain as well as decreasing the rate of OXPHOS. This effect was associated with the simultaneous down expression of two genes encoding proteins involved in the initiation phase of mitochondrial DNA transcription: POLRMT and TFB2M. Moreover, VERA induced down expression of genes coding for upstream key glycolytic enzymes, hexokinase and phosphofructokinase. These effects led to a reduced rate of ATP production associated with a cytotoxic effect. Given the significant implications of mitochondrial dysfunction for human health, it is crucial to consider the potential involvement of VERA in mitochondrial diseases.